Soybean yield, seed quality and thresh efficiency by mechanisation at different harvesting stages and postharvest ripening - Thi Thuy Hang Vu; Ngoc Thang Vu; Thi Tuyet Cham Le; Thi Ngoc Pham (Vietnam Journal of Science, Technology and Engineering, 2023)
This study determined the most appropriate and earliest soybean harvesting stage and the number of days of postharvest ripening with minimal effects on seed losses and quality when mechanical harvest and threshing were applied. Harvesting stages at four physiological maturities (60, 70, 80, and 90%) and various days of postharvest ripening treatment (1, 2, and 3 days) were applied for two soybean varieties DT12 and DT26. Harvesting at physiological maturity of 90% recorded the highest seed-shattering loss but the least seed damage (<5%) and highest seed quality, followed by a physiological maturity of 80%. There were no significant differences in seed yields between harvesting stages of 80 and 90% maturity. Harvesting soybeans at a physiological maturity of 60 and 70% resulted in no seed losses but a significant reduction in seed quality. To avoid adverse weather, an early harvest stage at a physiological maturity of 80% is suggested. Although postharvest ripening of soybeans for early harvest caused seed shattering losses (2-5%), it was necessary to ensure seed quality. These results indicate effective and practical methods for farmers at small households to use in early mechanical harvesting of soybeans.